A Comprehensive Study on the Etiology of Patients Receiving Cochlear Implantation With Special Emphasis on Genetic Epidemiology. Issue 2 (February 2016) - Miyagawa, Maiko; Nishio, Shin-Ya; Usami, Shin-Ichi
Abstract : Objective: Cochlear implantation is the most important treatment currently available for profound sensorineural hearing loss. The aim of this study was to investigate the etiology of hearing loss in patients with cochlear implantation, and to compare outcomes. Methods: Japanese hearing loss patients who received cochlear implants (CIs) or electric acoustic stimulation (EAS) in Shinshu University hospital (n = 173, prelingual onset: 92, postlingual onset: 81) participated in this study. Invader assay followed by the targeted exon-sequencing of 63 deafness genes using Massively parallel DNA sequencing (MPS) was applied. For prelingual patients, additional imaging examination, cCMV screening, and pediatric examination were performed for precise diagnosis. Results: Genetic screening successfully identified the causative mutation in 60% of patients with prelingual onset hearing loss and in 36% of those with postlingual hearing loss. Differences in the kinds of genes identified were observed between the two groups. Although there were marked variations in the outcome of cochlear implantation, patients with specific deafness gene mutations showed relatively good results. Conclusion: The present study showed genetic etiology is a major cause of hearing loss in CI/EAS patients. Patients possessing mutations in a number of deafness genes known to be expressed within inner ear have achieved satisfactory auditory performance, suggesting that the identification of the genetic background facilitates the prediction of post-CI performance. MPS is a powerful tool for the identification of causative deafness genes in patients receiving cochlear implantation. Therefore, determination of the involved region inside/outside of the cochlea by identification of the responsible gene is essential.